Pengembangan Sistem Point of Sales untuk Toko Emas berbasis Web (Studi Kasus: Toko Mas Leo) - Muhammad Arif Fadhilah; Nurudin Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Toko Mas Leo is a jewelry store in Boyolali, Central Java that has been established for 25 years. The owner of Toko Mas Leo explained that there are many risks that haunt the sale of jewelry, including theft by employees, recording errors, loss of jewelry, fraud with fake jewelry and notes, and so on. Some of these risks are caused by the way Mas Leo's records are still manual, starting from bookkeeping money, controlling jewelry stock to making transaction notes. Therefore, in this thesis research, a web-based point of sales system for gold jewelry stores is built that can calculate and record jewelry buying and selling transactions, which is integrated with the management of jewelry stock records and money bookkeeping. This system also has integration with a printer to print QR-coded transaction notes, as well as a camera to read QR codes from the notes. This system was developed using a prototyping approach and built on the Node.JS platform using the AdonisJS framework with the TypeScript programming language. The system has performed well and in accordance with the demands that have been described, according to the findings of unit testing using the base path testing approach and validation testing using the black-box approach. The results of usability testing using the system usability scale (SUS) approach resulted in a score of 73.21 which is classified as 'good' and 'acceptable', so it can be concluded that this system can be well received by potential users.